ESPÉCIES DE COCCINELLIDAE DA COLEÇÃO DO INSTITUTO AGRONÔMICO DE CAMPINAS - Chaves, Luiz Eduardo Leite; Berti Filho, Evoneo; Lourenção, André Luiz (REVISTA DE AGRICULTURA, 2015)
ESPÉCIES DE COCCINELLIDAE DA COLEÇÃO DO INSTITUTO AGRONÔMICO DE CAMPINAS